Effect of gluten‐free diet and compliance on quality of life in pediatric celiac disease patients. Issue 5 (27th March 2019) - Chellan, Deepak; Muktesh, Gaurav; Vaiphei, Kim; Berry, Neha; Dhaka, Narendra; Sinha, Saroj Kant; Thapa, Babu Ram; Kochhar, Rakesh
Abstract : Background: Quality of life (QOL) in children with celiac disease (CD) has been sparsely studied. Aims: We aimed to study QOL in pediatric CD and the effect of a gluten‐free diet (GFD) in a North Indian population. Methods: QOL was assessed at baseline and 6 months after GFD using a pediatric symptom checklist (PSC) score. The effect of GFD was assessed using a CD‐specific questionnaire on domains such as dietary compliance, parental behavior and perceptions, children's feeling, and difficulty identifying gluten‐free foods. Results: A total of 60 CD children (age 6.03 ± 0. 42 years, range: 2–12 years, M:F 2:1) were prospectively enrolled. The median PSC score at baseline was 11.5 (2–35), which showed a statistically significant improvement after GFD to 2.5 (0–34) ( P < 0.001). Significant concerns regarding specific domains emerged: difficulty in maintaining GFD 26.2%, at school 14.3%, at parties 43.2%, poor taste 11.4%, special diet a burden 28.5%, felt left out at school or friend's home 40.9%, felt different from other kids 40.9%, felt embarrassed to bring GFD to parties 54.6%, felt angry about following a special diet 56.8%, felt not invited out for meals because of CD 13.6%, and difficulty determining if food available was gluten free in 75%. Conclusion: GFD has a significant impact on emotional, behavioral, and psychosocial domains in children with CD. Proper labeling of commercially available food items, counseling, and patient support groups are the need of the hour. Abstract : We aimed to study the quality of life (QoL) in pediatric celiac disease (CD) and the effect of a gluten‐free diet (GFD) in a North Indian population. QoL was assessed at baseline and 6 months after GFD using the pediatric symptom checklist (PSC) score. The median PSC at baseline was 11.5 (2–35), which showed a statistically significant improvement after GFD to 2.5 (0–34) ( P < 0.001). GFD has a significant impact on emotional, behavioral, and psychosocial domains in children with CD.